Cooperative approaches to managing social responsibility in a market with externalities - FANG, Xin (Institutional Knowledge at Singapore Management University, 2020)
Problem definition: This paper studies two cooperative approaches of firms in managing social responsibility violations of their supplier: auditing a common supplier jointly (joint auditing) and sharing independent audit results with other firms (audit sharing). We study this problem in a market with externalities and a large number of firms. Academic/practical relevance: With numerous firms procuring their materials and parts worldwide, there are many cases in which overseas suppliers violate safety, labor, or environmental standards. Those violations have externalities in the sense that one firm’s violation affects other firms in the same market. It is not clear how such externalities affect competing firms’ incentives to cooperate and the effectiveness of such cooperation. Methodology: We develop a model based on a cooperative game in partition function form, which enables us to analyze the competitive and cooperative interactions of a large number of firms in a market. Results: Although there has been concern about cooperation for fear of compromising a competitive advantage, firms have incentives to cooperate in managing their suppliers when one firm can be hurt by others’ violations, that is, the negative externality is high. However, neither cooperative approach necessarily improves social responsibility, especially when one firm can benefit from others’ violations, that is, the positive externality is high. Finally, even if agreement is not reached for cooperation before conducting individual audits, social responsibility can still be improved by incentivizing firms to share their private audit results with others under a properly designed mechanism. Managerial implications: The careful assessment of the externalities associated with social responsibility violations is a key to the success of joint auditing and audit sharing. Although firms cooperate voluntarily in some cases, a government agency or an industry association should intervene in other cases to motivate cooperation if it is beneficial. In addition, caution must be taken to monitor manufacturers’ audit efforts, especially when cooperative approaches are implemented in the market where competition is fierce and consumers switch brands easily.